2010
DOI: 10.1016/j.ygyno.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab toxicities and their management in ovarian cancer

Abstract: Objectives The purpose of this review is to discuss the side effect profile of bevacizumab, to discuss proposed mechanisms of these toxicities, and to provide suggestions for management of adverse events. Methods A search of MEDLINE and ASCO and SGO abstract databases of articles published between January 1970 and August 2009 addressing the toxicity of bevacizumab in solid tumors was conducted. Reporting was limited to best available evidence including any available phase III studies and ovarian cancer phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 38 publications
(83 reference statements)
3
87
0
4
Order By: Relevance
“…This observation confirms that heavy pretreatment is an important factor involved in the occurrence of serious and fatal AEs, in clinical practice or in clinical trials (17,41).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This observation confirms that heavy pretreatment is an important factor involved in the occurrence of serious and fatal AEs, in clinical practice or in clinical trials (17,41).…”
Section: Discussionsupporting
confidence: 79%
“…This is likely due to the good performance status and relatively low incidence of pre-existing obstructive disease at the time of bevacizumab introduction in the current patients. Indeed, obstructive disease and peritoneal relapse have been reported to be the primary risk factors for GI perforation (45,46). Thus, the present results reveal that treating physicians are considering these known risk factors for bevacizumab toxicity before introducing the drug.…”
Section: Discussionmentioning
confidence: 53%
“…In fact, several FDA-approved TKIs that block VEGFRs, such as sunitinib, sorafenib, and pazopanib, are also commonly used antiangiogenic drugs in the clinic for treatment of human patients with RCC and other cancer types (37)(38)(39). Clinical experiences with bevacizumab and other anti-VEGF agents show that these drugs produce a range of adverse effects commonly seen in cancer patients, including hypertension, renal vascular injury often manifested by proteinuria and thrombotic microangiopathy, gastrointestinal perforation, and congestive heart failure (40)(41)(42). The anti-VEGF agent-induced broad adverse effects demonstrate that these drugs have a broad impact on vasculatures in multiple healthy tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies have reported incidence of 4.4% in bevacizumab-treated patients and 1.9% in non-bevacizumab-treated patients [38]. In a meta-analysis of 1,745 patients [39], the reported incidence of ATEs was 3.8% in patients treated with bevacizumab and 1.7% in patients treated without bevacizumab, with an absolute number of 5.5…”
Section: Arterial Thromboembolic Eventsmentioning
confidence: 98%